Evaluation of Extraction Methods on the Antioxidant Potential of Balik Angin Leaves Ethanol Extract (Alphitonia incana (Roxb.) Teijsm. & Binn. ex Kurz) - Putri Indah Sayakti; Hafiz Ramadhan; Dyera Forestryana; Eka Fitri Susiani; Nadya Aprillinia; Nadhia Khairany; Wardah Izzatul Awwaliyah; Winda Ameilia Dewi; Nur Syifa (Journal of Pharmascience, 2026)
Alphitonia incana, also known locally as balik angin, is an endemic natural antioxidant plant of Borneo. The objective of the present work was to compare the effectiveness of maceration and Soxhlet extraction of balik angin leaves with respect to antioxidant activity and phenolic–flavonoid content. Ethanolic extracts were prepared using both extraction methods, and the phenolic-flavonoid content was quantified spectrophotometrically. Antioxidant performance was assessed through DPPH, CUPRAC, and FRAP assays. The findings revealed that the Soxhlet-derived extract contained higher concentrations of phenolic-flavonoid compounds than those produced by maceration. In addition, the Soxhlet-derived extract demonstrated stronger antioxidant activity, as evidenced by lower IC₅₀ and EC₅₀ values in the DPPH (10.872 ppm) and CUPRAC (6.578 ppm) assays compared with the macerated extract (IC₅₀ 13.127 ppm; EC₅₀ 14.034 ppm) and was classified as a very strong antioxidant. The FRAP assay further supported these results, with ferric reducing power values of 1,484.1 mg AAE/g extract for the Soxhlet-derived extract and 1,295.8 mg AAE/g extract for the macerated sample. Overall, the study concludes that Soxhlet extraction is more effective than maceration in enhancing the antioxidant potential of balik angin leaf, a result that is closely associated with their elevated phenolic and flavonoid content.